The universal principle of grace: Feminism and anti-calvinism in two seventeenth-century women writers - Apetrei, S (2009)
This article presents one of the theological contexts for early feminist thought in England in the late seventeenth century. It argues that an emerging universalist soteriology in Platonist and radical thought had a positive impact on discourses about sexual equality, and shows how two female writers (the Quaker Elizabeth Bathurst and the visionary M. Marsin) combined their critique of the doctrine of limited atonement - in other words, the idea of an exclusive elect - with a confident assertion of women's calling to preach and teach in the Church. © The author 2009. Journal compilation © 2009 Blackwell Publishing Ltd.